Balancing making a difference with making a living in the conservation sector. Issue 3 (5th December 2021) - Pienkowski, Thomas; Keane, Aidan; Castelló y Tickell, Sofia; Hazenbosch, Mirjam; Arlidge, William N. S.; Baranyi, Gergő; Brittain, Stephanie; de Lange, Emiel; Khanyari, Munib; Papworth, Sarah; Milner‐Gulland, E. J.
Abstract: Goals play important roles in people's lives because they focus attention, mobilize effort, and sustain motivation. Understanding conservationists' satisfaction with goal progress may provide insights into real‐world environmental trends and flag risks to their well‐being and motivation. We asked 2694 conservationists working globally how satisfied they were with progress toward goals important to them. We then explored how this satisfaction varied among groups, including demographic and occupational. Finally, we looked at respondents' experiences associated with goal‐progress satisfaction. Many (94.0%) indicated that making a meaningful contribution to conservation was an important goal for them, and over half were satisfied or very satisfied in this area (52.5%). However, respondents were generally dissatisfied with progress on collective conservation goals (e.g., stopping species loss). Some groups were more likely to report dissatisfaction than others. For instance, those in conservation for longer tended to be less satisfied with collective goal progress (log odds –0.21, 95% credibility interval [CI] –0.32 to –0.10), but practitioners reported greater satisfaction (log odds 0.38, 95% CI 0.15–0.60). Likewise, those who were more optimistic in life (log odds 0.24, 95% CI 0.17–0.32), male (log odds 0.25, 95% CI 0.10–0.41), and working in conservation practice (log odds 0.25, 95% CI 0.08–0.43) reported greater satisfaction with individual goal progress. Free‐text responses suggested widespread dissatisfaction with livelihood goals, particularly related to job security and adequate compensation. Although contributing to conservation appeared to be a source of satisfaction, slow goal progress in other areas––particularly around making a living––looked to be a source of distress and demotivation. Employers, funders, professional societies, and others should consider ways to help those in the sector make a difference while making a satisfactory living by, for example, prioritizing conservationists′ well‐being when allocating funding. This support could include avoiding exploitative practices, fostering supportive work environments, and celebrating positive outcomes. Abstract : Article impact statement : Employers and funders should prioritize conservationists' well‐being, helping them make a difference while making a living. Abstract : El Balance entre Hacer una Diferencia y Ganarse la Vida en el Sector de la Conservación 21–323 Resumen: Los objetivos juegan un papel importante en la vida de las personas porque enfocan la atención, movilizan esfuerzos y mantienen la motivación. El entendimiento de la satisfacción de los conservacionistas con el progreso de sus objetivos podría proporcionar información sobre las tendencias ambientales del mundo real y marcar los riesgos para su bienestar y motivaciones. Les preguntamos a 2694 conservacionistas trabajando alrededor del mundo cuán satisfechos están con el progreso hacia los objetivos que consideran más importantes. Después exploramos cómo esta satisfacción varió entre grupos, incluyendo grupos demográficos y laborales. Finalmente, observamos las experiencias de los respondientes asociadas con la satisfacción con el progreso de los objetivos. Muchos (94%) indicaron que contribuir significativamente a la conservación es un objetivo importante para ellos, y más de la mitad estuvieron satisfechos o muy satisfechos en este campo (52.5%). Sin embargo, los respondientes también mostraron una inconformidad generalizada con el progreso de los objetivos colectivos de conservación (p. ej.: detener la pérdida de especies). Algunos grupos tuvieron una mayor probabilidad de reportar inconformidades que otros grupos. Por ejemplo, aquellos con mayor tiempo en la conservación tendieron a estar menos satisfechos con el progreso de los objetivos colectivos (probabilidad log ‐0.21, 95% intervalo de credibilidad [IC] ‐0.32 a ‐0.10), pero los practicantes reportaron una mayor satisfacción (probabilidad log 0.38, 95% IC 0.15‐0.60). De igual manera, quienes cuentan con mayor optimismo cotidiano (probabilidad log 0.24, 95% IC 0.17‐0.32), son de sexo masculino (probabilidad log 0.25, 95% IC 0.10‐0.41) y trabajan en la práctica de la conservación (probabilidad log 0.25, 95% IC 0.08‐0.43) reportaron una mayor satisfacción con el progreso de los objetivos individuales. Las respuestas de texto libre sugirieron una inconformidad generalizada con los objetivos de sustento, particularmente los relacionados con la seguridad laboral y las compensaciones adecuadas. Aunque contribuir a la conservación parece ser una fuente de satisfacción, el progreso lento de los objetivos en otras áreas – particularmente las relacionadas con ganarse la vida – indicaba ser una fuente de angustia y desmotivación. Los empleadores, financiadores, las sociedades profesionales y demás deberían considerar maneras para ayudar a aquellos en el sector de la conservación a lograr una diferencia a la vez que se ganan la vida satisfactoriamente, por ejemplo, mediante la priorización del bienestar de los conservacionistas al momento de asignar financiamientos. Este apoyo podría incluir evitar prácticas explotadoras, fomentar ambientes de trabajo solidarios y celebrar los resultados positivos. 保护工作中有所作为与谋取营生的平衡: 【摘要】 目标在人们的生活中起着重要的作用, 因为它能帮助人们集中注意力, 调动工作积极性和维持动力。了解保护工作者对目标进展的满意度, 可能有助于深入理解现实世界的环境变化趋势, 并明确保护工作者的福祉和动机面临的风险。我们调查了全球2694名保护工作者关于他们关注的重要目标进展情况的满意度, 并探讨了这种满意度在不同群体(不同人口结构和职业)之间的差异。最后, 我们研究了与目标进展满意度相关的受访者经历。许多受访者(94.0%)表示, 为保护作出有意义的贡献是他们的重要目标, 且超过半数的受访者(52.5%)在这方面感到满意或非常满意。然而, 受访者普遍对共同保护目标(如遏止物种丧失)的进展表示不满意。一些群体比其他群体更有可能报告不满意的结果, 例如, 从事保护工作时间较长的受访者往往对共同目标的进展不太满意(比率比对数为‐0.21, 95%置信区间[CI]为‐0.32至‐0.10), 但工作时间较短的保护工作者的满意度则较高(比率比对数0.38, 95% CI 0.15‐0.60)。同样地, 那些在生活更乐观的人(比率比对数0.24, 95%置信区间0.17‐0.32)、男性(比率比对数0.25, 95% CI 0.10‐0.41), 以及从事保护工作的受访者(比率比对数0.25, 95% CI 0.08‐0.43)对个人目标的进展的满意度普遍更高。自由文本的回答表明, 受访者普遍对生计目标不满意, 尤其是在工作保障和适当补偿方面。虽然对保护工作的贡献似乎可以提供满足感, 但其它领域的目标进展缓慢(特别是围绕生计的目标), 则可能引发了忧虑和积极性不足。雇主、资助者及专业团体等应考虑如何帮助保护工作者在过上满意的生活的同时有所成就, 例如, 在资金分配中优先考虑保护工作者的福利。这种支持还可以包括避免剥削性工作, 建立支持性的工作环境, 以及庆祝积极的保护成果。【翻译:胡怡思;审校:聂永刚】 关键词 :保护目标、保护心理学、保护工作者的福祉、目标进展满意度、动机、职业健康、反思性